CHBP-loaded mesoporous polydopamine nanoparticles attenuate neuroinflammation and reprogram microglia-neuron crosstalk for spinal cord injury repair - Linyi Xiang; Jiacheng Zhang; Yuzhe Wu; Jingwei Shi; Yun Shu; Ruize Miu; Jiayi Zhao; Junsheng Zhu; Zhichao Tao; Yibo Geng; Haojie Zhang; Zhenglin Li; et al. (Chemical Engineering Journal, 2026)

Loss analysis and performance optimization of high-efficiency G-M type pulse tube cryocoolers operating at liquid helium temperatures - Ruize Li; Haoren Wang; Zhicai Zhang; Kaihao Zhang; Qinyu Zhao; Qingnan Zhang; Ming Wu; Bo Wang; Tao Jin; Zhihua Gan (International Journal of Refrigeration, 2026)

BN-enhanced supramolecular polymer dielectrics with ultrahigh energy density at 200 °C - Tao Lu; Jinfeng Li; Ruize Wang; Shiqi Wang; Tian Zhang (Chemical Engineering Journal, 2026)

Discovery and Optimisation of Novel Bombinin-Derived Peptides from Bombina variegata against Staphylococcus aureus - Jiachen Liu; Keyi Yao; Ruize Sun; Xiaonan Ma; Chengbang Ma; Xiaoling Chen; Yangyang Jiang; Tao Wang; Tianbao Chen; Chris Shaw; Mei Zhou; Lei Wang (Probiotics and Antimicrobial Proteins, 2026)
Amphibian skin-secreted antimicrobial peptides (AMPs) have garnered significant attention for their excellent biological activity and low propensity for drug resistance over the past 40 years. Bombinins and bombinin H, two classes of AMPs isolated from the skin secretions of Bombina species, demonstrate strong antimicrobial activity against broad-spectrum microorganisms. In this study, two novel peptides, bombinin-like peptide 7S and bombinin-H2L, were identified from the toad, Bombina variegata . While both peptides exhibited broad-spectrum antimicrobial activity, they also showed relatively high cytotoxicity. To explore the structure–activity relationship and enhance therapeutic potential, bombinin-H2L, which displayed stronger average antimicrobial activity, was used as a template. With the aid of bioinformatics analysis, a series of bombinin-H2L analogues were designed by increasing the net positive charges and/or adjusting the amphiphilicity of the parent peptide. Among these analogues, [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L demonstrated high therapeutic efficacy and specificity toward clinically isolated, drug-resistant Staphylococcus aureus strains in both in vitro and ex vivo tests. Their notable biosafety profiles, sensitivity to diverse environments, and ability to disrupt biofilms highlight their potential for further development. Additionally, studies on the mechanism of [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L revealed a membrane-targeted antimicrobial mechanism, with its antibacterial function exerted by disrupting the integrity of bacterial membranes. These findings provide valuable insights into structural modifications of bombinin H peptides for enhanced activity, and [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L have the potential as promising candidates for novel antibacterial agents in treated bacterial skin infections.

Charcoal-derived hard carbon anodes with enhanced sodium storage performance for sodium-ion batteries - Shengchen Yang; Yan Li; Chun Chen; Hui Wang; Kaihang Wang; Qingqing Li; Ruize Dong; Manman Chen; Cai Zhao; Weiwei Xu; Lin Sun; Tao Zhang; et al. (Chemical Engineering Journal, 2025)

The impacts of polypropylene microplastics on carbon and nitrogen cycling in coastal wetlands: Field evidence - Feng Yuan; Yue Xue; Zhuoyue Zhang; Jianguo Tao; Yuyang Song; Hongyu Chen; Qihang Liao; Haiyan Lin; Ming Lu; Yongcheng Ding; Teng Wang; Ruize Yang; et al. (Journal of Hazardous Materials, 2025)

Correction: Biological characterization of emerging fungal pathogen Colletotrichum associated with mango (Mangifera indica L.) post-harvest anthracnose from Vietnam - Ruize Tao; Bingjuan Yang; Li Lin; Shahzad Munir; Yuchuan Li; Xi Wang; Min Huang (Molecular Biology Reports, 2024)

Biological characterization of emerging fungal pathogen Colletotrichum associated with mango (Mangifera indica L.) post-harvest anthracnose from Vietnam - Ruize Tao; Bingjuan Yang; Li Lin; Shahzad Munir; Yuchuan Li; Xi Wang; Min Huang (Molecular Biology Reports, 2024)

Experimental Investigation on Near-Field Acoustic Propagation Characteristics of Leakage Detection in Submarine Pipelines - Kang Zhang; Ruize Ma; Tao Geng; Jiannan Yang; Yongjun Gong (Journal of Marine Science and Engineering, 2023)
The leakage of subsea oil and gas pipelines can have adverse impacts on production progress and the ecological environment. Investigating the sound source and near-field sound propagation of pipeline leaks is essential for understanding the acoustic characteristics of and variations in these leaks. Such understanding is significant for the accurate detection and location of small leaks in pipelines. In this study, we designed an experimental system to study the characteristics of leakage sound signals. We introduced the formation mechanism of leakage sound sources and reviewed corresponding theoretical research. The leakage sound signal’s characteristic frequency range was determined to be between 1 kHz and 2 kHz. We examined the effects of pipeline pressure, leakage aperture, and detection distance on the acoustic signal characteristics. The results show that as internal pipe pressure increases, the leakage sound signal intensity first increases and then decreases. As the leakage aperture increases, the intensity of the leakage sound signal increases. Within a short distance, the intensity remains consistent regardless of detection distance. The results of this experimental study can guide the acoustic internal detection of pipelines. This study has practical significance in the timely detection of small leaks in pipelines and preventing leakage accidents from occurring.